Claiming a Pedagogy of Interruption through International Experiences. Issue 3 (3rd July 2019) - Thompson, Ashleigh B.
ABSTRACT: This essay shares impressions from French and German higher education through a comparative US lens, with a special focus on internationalization and mobility. The author integrates the theoretical lens of Gert Biesta's Pedagogy of Interruption to posit that international experiences facilitate encounters with otherness that spark new ways of seeing and thinking. These disruptive experiences can be particularly generative in education, which fosters reflective practice, and for teacher educators themselves. Key questions for considering international approaches to teacher education touch on themes such as global citizenship, relationality, student diversity and transnational partnership.